Implementation of the Provisions of the Cluster Theory into the Accounting System: Genesis and Evolution - VYSOCHAN, Oleh; STANASIUK, Natalia; HONCHAR, Svitlana; HYK, Vasyl; VYSOCHAN, Olha (Theoretical and Practical Research in Economic Fields; Vol 15 No 1 (2024): TPREF, Volume XV, Issue 1(29), Spring 2024DO - 10.14505/tpref.v15.1(29).01, 2024)
In current economic conditions, a large number of enterprises carry out their activities by joining into network (cluster) structures, which is one of the means of improving competitive relations in the external environment. To ensure the integration of the interests of participants in network structures by increasing the coordination and controllability of interactions, a significant place is given to the accounting system as the main source of information. The article aims to study the theoretical and methodological foundations of implementing the cluster economy concept in the accounting system. The methodological basis is the fundamental provisions of modern economic institutional theory and scientific works of scientists. As a result of the research, it was possible to analyze the historical aspects of the development of accounting support for managing cluster structures. The areas of development of accounting based on the provisions of economic theory and taking into account the specific features of cluster structures are identified and substantiated.